2008
DOI: 10.1016/j.ijsolstr.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Ductile–brittle transitions in the fracture of plastically-deforming, adhesively-bonded structures. Part I: Experimental studies

Abstract: Rate effects for adhesively-bonded joints in steel sheets failing by mode-I fracture and plastic deformation were examined. Three types of test geometries were used to provide a range of crack velocities between 0.1 and 5000 mm/s: a DCB geometry under displacement control, a wedge geometry under displacement control, and a wedge geometry loaded under impact conditions. Two fracture modes were observed: quasi-static crack growth and dynamic crack growth. The quasistatic crack growth was associated with a toughe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 15 publications
2
38
2
Order By: Relevance
“…In these studies, plastic deformation of the steel always accompanied fracture. The mode-I studies (Sun et al, 2008a) exhibited crack growth that was contained completely within the adhesive layer. The mode-I properties of the adhesive layer were determined to be essentially rate-independent, except in one important regard: as the crack velocity increased, there was an increased tendency for a catastrophic transition to a relatively brittle mode of fracture.…”
Section: Background and Motivationmentioning
confidence: 98%
See 2 more Smart Citations
“…In these studies, plastic deformation of the steel always accompanied fracture. The mode-I studies (Sun et al, 2008a) exhibited crack growth that was contained completely within the adhesive layer. The mode-I properties of the adhesive layer were determined to be essentially rate-independent, except in one important regard: as the crack velocity increased, there was an increased tendency for a catastrophic transition to a relatively brittle mode of fracture.…”
Section: Background and Motivationmentioning
confidence: 98%
“…There was a considerable range of crack velocities for the quasi-static mode after transitions to dynamic fracture occurred, but it should be noted that quasistatic crack growth did occur at a velocity very comparable to the average specimen velocity, even at the fastest rate. It was noted that transitions to dynamic fracture were not as prevalent for these mode-I "adhesive" failures at the interface as they had been for mode-I "cohesive" crack growth within the adhesive layer (Sun et al, 2008a). Figure 13, shows that when the crack was growing in a quasi-static mode, the distance between the crack tip and the wedge was in the range of 6 to 10 mm with no correlation to crack velocity (outside specimen-to-specimen variation), but increased to between 16 and 24 mm immediately after a transition to dynamic fracture.…”
Section: Asymmetric Wedge Geometry and The Toughness Of The Brittle Modementioning
confidence: 98%
See 1 more Smart Citation
“…The results showed good agreement with experiments with respect to the stiffness and the peak load but overestimated the crack propagation load. The cohesive parameters for both tough and brittle modes of crack growth were determined in the work of Sun et al [22,23] by comparing numerical predictions from cohesive zone simulations to the experimental results obtained using DCB specimens and tensile tests. Li et al [24] used a cohesive--zone approach to model the mode I fracture of adhesively bonded composite joints.…”
Section: Application Of the Czm To Adhesive Jointsmentioning
confidence: 99%
“…Rate-dependent CZMs have been used extensively to model the fracture of ratedependent materials in general [e.g. [19][20][21][22][23][24][25][26][27][28][29].However, only a few authors have reported the use of rate-dependent CZMs to study the fracture of adhesive joints [15,[30][31][32][33][34][35]. For example, to capture the rate-dependency of failure in adhesive bonds of the double cantilever-beam test specimen, Xuet.…”
Section: Introductionmentioning
confidence: 99%